The application of walking training in the rehabilitation of patients after coronary artery bypass grafting - Sobczak, Dorota; Dylewicz, Piotr (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2015)
Walking is regarded as one of the most common and utilitarian activities of everyday life. Rehabilitation programs developed on the basis of this form of activity often constitute the primary method of rehabilitating patients after coronary artery bypass grafting. This paper provides a review of literature concerning various forms of walking training, discussing their impact on the parameters of exercise capacity and verifying the training methods with regard to the current guidelines. Attention is drawn to the diversity of the exercise protocols applied during the early and late stages of rehabilitation and pre-rehabilitation programs including: treadmill walking, walking down the corridor, treadmill walking enriched with virtual reality, and walking as an element of training sessions consisting of many different forms of activities. Exercise protocols were also analyzed in terms of their safety, especially in the case of high-intensity interval training. Despite the variety of the available rehabilitation programs, the training methodology requires constant improvement, particularly in terms of load dosage and the supervision of training sessions.